Analisis Pengaruh Profil Budaya Organisasi Terhadap Kualitas Pelayanan - Dina Rahmayanti; Alizar Hasan; Zuchria Anggia Sari Hasnda (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Improving performance of the company can be done by services increasing provided to the customer. Each of the activities carried out by the service personnel must be guided by the established rules of the organization and the organization's values. The values of the organization referred to organizational culture. The aim of this study was to determine the level of organizational culture profile and the quality of service and work culture variables that most influence on quality service. The research was conducted using survey research method by distributing questionnaires to employees in UNAND. The questionnaire in the form of closed questions using a Likert scale, which consists of three parts, namely respondent characteristics (part 1), organizational culture variables (section 2) and the variable quality of service (section 3). In this research, the cultural variables that affect the quality of service by using the linear regression method. From the research that has been conducted, showed that the level of organizational culture profile applied by Andalas University as a whole is at 3:43 or are at a good level and for the level of quality of service at 4:11 which is at a good level.Keywords: organization, profile organizational culture, service quality, regresion, andalas university